(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article explores a group of verbs that share semantic relationships in both the English and Uzbek languages. By analyzing the similarities and differences in the usage and meaning of these verbs across the two linguistic systems, the study aims to uncover insights into the underlying structures that govern semantic connections in verb usage. The comparative analysis provides a valuable cross-cultural perspective, shedding light on the intricacies of language-specific nuances and contributing to a deeper understanding of the semantic dimensions within verb categories.